Intrachromosomal excision of a hybrid Ds element induces large genomic deletions in Arabidopsis - Page, Damian R. (Proc Natl Acad Sci U S A, 2004)
Transposon activity is known to cause chromosome rearrangements in the host genome. Surprisingly, extremely little is known about Dissociation (Ds)-induced chromosome rearrangements in Arabidopsis, where Ds is intensively used for insertional mutagenesis. Here, we describe three Arabidopsis mutants with reduced fertility and propose that excision of a hybrid Ds element induced a large genomic deletion flanking Ds. In the mutants anat and haumea, the deletion mechanism consists of a local Ds transposition from replicated into unreplicated DNA followed by Ds excision, where one end of the newly transposed element and one end of the Ds transposon at the donor site served as substrate for transposase. Excision of this hybrid element reminiscent of a macrotransposon leads to loss of the chromosomal piece located between the two ends, including one full Ds element and the flanking genomic sequence. This mechanism was found to be responsible for several other deletions and occurs at a genetically trackable frequency. Thus, it could be applied to efficiently generate deletions of various sizes in the vicinity of any existing Ds element present in the genome. In the mutant tons missing, a mechanism that involves endogenous repetitive sequences caused a large flanking deletion at a position unlinked to the starter locus. Our study of Ds transposition in Arabidopsis revealed previously undescribed mechanisms that lead to large genomic deletions flanking Ds elements, which may contribute to genome dynamics and evolution.